DESIGNING THE INTERIOR OF CANDI LOKA NGAWI RESTAURANT BY APPLYING THE BATIK JAMUS TEA MOTIF THEME - Anam Nur Cahyono; Indarto Indarto (Institut Seni Indonesia Surakarta, 2020)
The application of the Jamus Tea motif batik theme in the interior design of Candi Loka Restaurant in Ngawi is an effort to accommodate the needs of visitors to the Jamus Tea Plantation tourism object to enjoy the processed tea. This work aims to create a comfortable interior design of Candi Loka Restaurant and apply a contemporary style. In this work, the theme of the Jamus Tea batik motif is applied through the Kurtz programming method. The result of this work is the interior design of Candi Loka Restaurant, which includes lobby facilities, dining area, teashop, workshop and education area, management office, kitchen, rest area, warehouse, prayer room, and toilet. The results of this work can be a reference for interior designers in designing contemporary interior concepts based on local wisdom